Performance Modelling and Evaluation of a Telecommunication Contact Centre: A Queuing Theory Approach - , B, Balakrishnan; S, Munisamy, (Malaysian Journal of Science, 2007)
A call centre is a centralised office of a company that mainly handles incoming telephone calls from customers via telephone. The call centre basically functions as a primary contact point between customers and their service providers. Call centres are highly technology driven. However, surprisingly, most of the costs incurred in a call centre are due to human resources. Customer service agents who handle the calls form most of the human resource component in a contact centre. An important goal of the call centre is to provide a good level of customer service. A good customer service level will ensure customer satisfaction so that customers will return. The consequence of making customers wait too long may be lost profit from lost business opportunities. In this context, queuing models are important to determine the appropriate number of customer service agents that strike a balance between the two conflicting objectives of cost reduction and provision of good service. In this research, we have attempted to build a queuing model to evaluate the performance of a call centre that belongs to one of Malaysia's leading telecommunication service providers and to allocate its human resources. The telephone calls coming in to the call centre are the customers in large queuing system, and the customer service agents are the servers. The telephone calls that arrived on a Monday during the peak period fitted the assumptions underlying the Erlang C or the M/M/s model in terms of arrival pattern and service time. The model built then was used to analyse the call centres' operating characteristics and to decide various numbers of staffs required to achieve different management objectives.